2015
DOI: 10.1093/hmg/ddv353
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-structural time-course study in theC. elegansmodel for Duchenne muscular dystrophy highlights a crucial role for sarcomere-anchoring structures and sarcolemma integrity in the earliest steps of the muscle degeneration process

Abstract: Duchenne muscular dystrophy (DMD) is a genetic disease characterized by progressive muscle degeneration due to mutations in the dystrophin gene. In spite of great advances in the design of curative treatments, most patients currently receive palliative therapies with steroid molecules such as prednisone or deflazacort thought to act through their immunosuppressive properties. These molecules only slightly slow down the progression of the disease and lead to severe side effects. Fundamental research is still ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 75 publications
9
45
0
1
Order By: Relevance
“…However, the amount of muscle cell death (referred hereafter as muscle degeneration) significantly increased when a dys-1 loss-of-function mutation was combined with a hypomorphic mutation in the hlh-1 gene (Gieseler et al, 2000). In addition, muscle degeneration Development, structure, and maintenance of C. elegans body wall muscle increases in both the dys-1(cx18) single mutant and the dys-1(cx18); hlh-1(cc561) double mutant with higher body bending forces on firm culture medium, supporting the hypothesis of a mechanical role for DYS-1 (Brouilly et al, 2015). This result is in agreement with studies performed in dystrophin deficient mdx mice that revealed a higher vulnerability and enhanced dystrophic progression in response to exercise (Brussee et al, 1997;De Luca et al, 2003).…”
Section: The Function Of Dys-1 In Dense Body and Sarcolemma Integritymentioning
confidence: 77%
See 3 more Smart Citations
“…However, the amount of muscle cell death (referred hereafter as muscle degeneration) significantly increased when a dys-1 loss-of-function mutation was combined with a hypomorphic mutation in the hlh-1 gene (Gieseler et al, 2000). In addition, muscle degeneration Development, structure, and maintenance of C. elegans body wall muscle increases in both the dys-1(cx18) single mutant and the dys-1(cx18); hlh-1(cc561) double mutant with higher body bending forces on firm culture medium, supporting the hypothesis of a mechanical role for DYS-1 (Brouilly et al, 2015). This result is in agreement with studies performed in dystrophin deficient mdx mice that revealed a higher vulnerability and enhanced dystrophic progression in response to exercise (Brussee et al, 1997;De Luca et al, 2003).…”
Section: The Function Of Dys-1 In Dense Body and Sarcolemma Integritymentioning
confidence: 77%
“…The contribution of mechanical forces and movement to DYS-1 dependent muscle degeneration is further supported by a reduction of muscle degeneration in adult dys-1; hlh-1 double mutants when sarcomere contraction is inhibited by mutations in different genes affecting the myofilament lattice (Mariol et al, 2007), RNAi mediated knock down of the EGL-19 L-type voltage gated Ca 2+ channel (Mariol and SĂ©galat 2001), or after forced immobilization by treatment with muscimol, a GABAA agonist and anesthetic used to paralyze C. elegans (Brouilly et al, 2015). Similarly, limb immobilization or treatment with muscle relaxants prevent and reduce the occurrence of muscle degeneration in mdx mice (Mokhtarian et al, 1999).…”
Section: The Function Of Dys-1 In Dense Body and Sarcolemma Integritymentioning
confidence: 95%
See 2 more Smart Citations
“…Michel Labouesse (IBPS, Paris, France) showed that during embryonic elongation driven by muscle contraction, the apical extracellular matrix contributes to maintaining tissue integrity and distributing stress. He also provided insights into the degeneration of muscle cells induced by physical exercise in dystrophin mutants (Brouilly et al, 2015). Sara Wickström (MPI, Cologne, Germany) showed how extrinsic forces lead to attenuation of transcription, chromatin changes and silencing of Polycomb target genes in human epidermal progenitor cells (Le et al, 2016).…”
Section: Biomechanical and Bioelectrical Control Of Regenerationmentioning
confidence: 99%